Employee Engagement in HRM: A Bibliometric Study - Loso Judijanto (Westscience Press, 2026)
This study examines the development and intellectual structure of employee engagement research within the field of human resource management through a bibliometric approach. Using data retrieved from a major academic database, the analysis covers publications over a defined period and applies performance analysis and science mapping techniques. The findings show that human resource management remains the central foundation of the literature, closely linked with performance, productivity, and organizational outcomes. The mapping also reveals distinct yet interconnected research streams, including employee-centered outcomes such as work engagement and leadership, sustainability-oriented approaches such as green human resource management, and emerging technology-driven themes such as artificial intelligence and predictive analytics. Over time, the field has shifted from a primary focus on behavioral and performance aspects toward more integrative perspectives that incorporate sustainability and digital transformation. These patterns indicate that employee engagement is increasingly understood within a broader system that connects human, organizational, and technological dimensions. This study provides a structured overview of the field and highlights potential directions for future research, particularly in exploring the intersection between digital human resource management, sustainability practices, and employee engagement.